2002
DOI: 10.1046/j.0003-2409.2001.02409.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the addition of ketamine to morphine in patient‐controlled analgesia

Abstract: SummaryThis randomised, double-blind, prospective study compared morphine (1 mg.m ) with the combination of morphine (1 mg.m )1 ) and ketamine (0.75 mg.m )1 ) via a patient-controlled analgesia system (PCAS) for postoperative pain control. A total of 42 female patients, ASA grade I and II, undergoing elective total abdominal hysterectomy was studied. During a standardised anaesthetic, a loading dose from the PCA syringe of 10 ml.m )2 of body surface area was given. A PCAS with a background infusion was commenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 31 publications
(46 reference statements)
2
35
0
1
Order By: Relevance
“…Unlügenç, et al18 studied patients after major abdominal surgery and found that ketamine 1 mg/mL added to tramadol 5 mg/mL IV-PCA (loading dose 1 mg/kg, bolus 0.2 mg/kg, lockout 20 min, background infusion 0.4 mg/kg/h) improved analgesia and reduced tramadol consumption. However, investigating patients undergoing total abdominal hysterectomy, Murdoch, et al19 did not find any benefit of adding ketamine 0.75 mg/mL to morphine 1 mg/mL IV-PCA (10 mL/m 2 body surface area of loading dose, bolus 1 mL, lockout 5 min, background infusion 1 mL/h). Reeves, et al20 found no pain-reducing or morphine-sparing benefits of ketamine bolus 1 mg/mL plus morphine 1 mg/mL IV-PCA (bolus, lockout, and background infusions were determined by the anesthesiologists) in patients after major abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Unlügenç, et al18 studied patients after major abdominal surgery and found that ketamine 1 mg/mL added to tramadol 5 mg/mL IV-PCA (loading dose 1 mg/kg, bolus 0.2 mg/kg, lockout 20 min, background infusion 0.4 mg/kg/h) improved analgesia and reduced tramadol consumption. However, investigating patients undergoing total abdominal hysterectomy, Murdoch, et al19 did not find any benefit of adding ketamine 0.75 mg/mL to morphine 1 mg/mL IV-PCA (10 mL/m 2 body surface area of loading dose, bolus 1 mL, lockout 5 min, background infusion 1 mL/h). Reeves, et al20 found no pain-reducing or morphine-sparing benefits of ketamine bolus 1 mg/mL plus morphine 1 mg/mL IV-PCA (bolus, lockout, and background infusions were determined by the anesthesiologists) in patients after major abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary 18,[20][21][22][25][26][27]29,30,32,34,36,40,41,44,45,50 cardiac or thoracic surgery (six trials), 19,23,35,37,38,53 orthopedic surgery (ten trials), 24,28,31,33,39,43,[47][48][49]51 and other surgery (three trials). 42,46,52 General anesthesia was used in 34 trials; one trial used PCA during and after a uterine artery embolization procedure, 29 and one used either general or regional anesthesia.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…In regard to pruritus, the incidences in the HO group and the HK group were 7/22 (32%) and 1/22 (5%), respectively, and it was approximately seven times more prevalent in the HO group. Javery et al [25] and Murdoch et al [26] have also reported the reduction of pruritus in the group receiving additional ketamine. Such effects of ketamine have been reported to be due to the suppression of the central sensitization and reduced tolerance to opioid analgesics.…”
Section: Discussionmentioning
confidence: 99%